CdS / NV-g-C3N4 heterojunction photocatalytic material, preparation method thereof and application of CdS / NV-g-C3N4 heterojunction photocatalytic material in degradation of sulfonamide pollutants
By preparing CdS/NV-g-C3N4 heterojunction photocatalytic material, the problem of insufficient activity of existing g-C3N4 photocatalysts is solved, efficient degradation of sulfonamide pollutants is achieved, and photocatalytic efficiency and carriers are improved. life.
Patent Information
- Application Number
- CN202411429907.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-11
AI Technical Summary
The photocatalytic activity of existing graphite carbon nitride (g-C3N4) photocatalysts is limited by rapid recombination of photogenerated charges, large sample size and low specific surface area, making it difficult to effectively degrade sulfonamide pollutants.
Tablet g-C3N4 was prepared by calcining melamine, and calcining under an argon and hydrogen atmosphere to form NV-g-C3N4, and then hydrothermal reaction with sodium sulfide and cadmium acetate to form CdS/NV-g-C3N4 heterojunction Photocatalytic materials.
This heterojunction photocatalytic material improves the efficiency of light absorption and current output by forming a heterojunction structure. Compared with the original g-C3N4, the energy conversion efficiency is greatly improved, and the carrier life is greatly extended, which significantly improves the The degradation efficiency of sulfonamide pollutants.
Smart Images

Figure CN119406436A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to a CdS / NV-gC 3 N 4 Heterojunction photocatalytic material, preparation method thereof and application in degradation of sulfonamide pollutants. Background Art
[0002] As an important green chemical technology, photocatalysis has received increasing attention in recent years. With the global emphasis on environmental protection and sustainable development, the problems of traditional energy consumption and environmental pollution have become increasingly prominent, and there is an urgent need to find new clean energy and pollution control methods. The basic principle of photocatalysis is that the electron-hole pairs generated by photocatalysts under light can react with water or other reactants to achieve the degradation of pollutants and the generation of clean energy. Photocatalytic technology can effectively promote chemical reactions and reduce dependence on fossil fuels by utilizing sunlight, a renewable energy source, providing an environmentally friendly solution. In recent years, researchers have continuously explored the synthesis and modification of new photocatalysts to improve their photocatalytic efficiency and stability.
[0003] Graphite Carbon Nitride (gC 3 N 4 ) is a metal-free polymer photocatalyst with a large conjugated π structure, which has attracted widespread attention due to its stable chemical properties and simple preparation. 3 N 4 The photocatalytic activity of gC is limited by the rapid recombination of photogenerated charges, large sample size and low specific surface area. 3 N 4 The photocatalytic activity of organic compounds has attracted more and more attention from technicians in this field. Summary of the invention
[0004] In order to solve or partially solve the problems existing in the related art, the present invention provides a CdS / NV-gC 3 N 4 Heterojunction photocatalytic material, preparation method thereof and application in degradation of sulfonamide pollutants.
[0005] The present invention provides a CdS / NV-gC 3 N 4 A method for preparing a heterojunction photocatalytic material, comprising: Step a), calcining melamine to obtain flake gC 3 N 4 , the flake gC 3 N 4 Grinding, washing, centrifugation, drying and secondary grinding are performed to obtain gC 3 N4 powder; Step b), the gC 3 N 4 The powder was calcined in an argon and hydrogen atmosphere to obtain NV-gC 3 N 4 powder; Step c), mixing sodium sulfide and cadmium acetate in pure water, and then adding the NV-gC 3 N 4 powder, to obtain NV-gC 3 N 4 and a solid-liquid mixture of CdS; Step d), placing the solid-liquid mixture in a reactor for hydrothermal reaction, centrifuging, washing, drying and grinding the reaction mixture to obtain CdS / NV-gC 3 N 4 Heterojunction photocatalytic materials.
[0006] Furthermore, in the step a), the calcination temperature is 500-600° C., the time is 3.3-4.5 hours, and the heating rate is 1-10° C. / min.
[0007] Furthermore, in the step b), the volume ratio of argon to hydrogen is 10:1, the calcination temperature is 500-600°C, the time is 0.5-1.5h, and the heating rate is 1-10°C / min.
[0008] Furthermore, in the step c), gC 3 N 4 The mass ratio of powder, cadmium acetate and sodium sulfide is (95~105):(1.6~3.6):(2~4).
[0009] Furthermore, in the step d), the temperature of the hydrothermal reaction is 155-165° C., and the time is 11-13 hours.
[0010] Furthermore, in the steps a) and d), the drying temperature is 60-80°C.
[0011] Furthermore, in the steps a) and d), the cleaning is specifically: washing with water and ethanol alternately 2 to 3 times.
[0012] The present invention also provides a CdS / NV-gC 3 N 4 The heterojunction photocatalytic material is prepared according to any of the methods described above.
[0013] The present invention also provides a CdS / NV-gC 3 N 4Application of heterojunction photocatalytic materials in the degradation of sulfonamide pollutants.
[0014] Furthermore, the application includes: The CdS / NV-gC of claim 8 3 N 4 The heterojunction photocatalytic material and the persulfate are mixed and uniformly dispersed in the sewage containing sulfonamide pollutants to obtain a water body to be treated; A xenon lamp equipped with a 400 nm filter is used as a light source to perform light treatment on the water body to be treated.
[0015] The CdS / NV-gC provided by the present invention 3 N 4 Heterojunction photocatalytic materials and preparation methods thereof may include the following beneficial effects: 1. The preparation method uses melamine as a precursor to prepare NV-gC 3 N 4 , and then bonded tightly with cadmium sulfide through hydrothermal method to form a heterojunction. 3 N 4 It has good light absorption and photogenerated charge separation capabilities, while Cds has high conductivity and tunable surface properties. The heterojunction photocatalytic material formed by the two can promote light absorption and current output, greatly improving the energy conversion efficiency and greatly extending the carrier life compared to the original carbon nitride.
[0016] 2. The preparation method has the advantages of simple operation, mild reaction conditions, no pollution to the environment, and high catalytic activity of the product, so it can be widely used.
[0017] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.
[0019] Figure 1 gC prepared in Example 1 of the present invention 3 N 4 SEM images of Figure 2 NV-gC prepared in Example 1 of the present invention 3 N 4 SEM images of Figure 3The CdS / NV-gC prepared in Example 1 of the present invention 3 N 4 SEM image of heterojunction photocatalytic material; Figure 4 The CdS / NV-gC prepared in Example 1 of the present invention 3 N 4 The effect diagram of heterojunction photocatalytic material activating persulfate composite system to degrade sulfonamide pollutants; Figure 5 It is gC 3 N 4 NV-gC 3 N 4 、CdS / NV-gC 3 N 4 Graph showing the effect of activated persulfate composite system on degradation of sulfamethoxazole. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] The terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The singular forms "a", "the" and "the" used in the present invention and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0022] It should be understood that although the terms "first", "second", "third", etc. may be used to describe various information in the present invention, such information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of the present invention, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0023] The present invention provides a CdS / NV-gC 3 N 4 A method for preparing a heterojunction photocatalytic material, comprising: Step a), calcining melamine to obtain flake gC 3 N 4 , the flake gC 3 N 4 Grinding, washing, centrifugation, drying and secondary grinding are performed to obtain gC 3 N 4 powder; Step b), the gC 3 N 4 The powder was calcined in an argon and hydrogen atmosphere to obtain NV-gC 3 N 4 powder; Step c), mixing sodium sulfide and cadmium acetate in pure water, and then adding the NV-gC 3 N 4 powder, to obtain NV-gC 3 N 4 and a solid-liquid mixture of CdS; Step d), placing the solid-liquid mixture in a reactor for hydrothermal reaction, centrifuging, washing, drying and grinding the reaction mixture to obtain CdS / NV-gC 3 N 4 Heterojunction photocatalytic materials.
[0024] The above step a) is a step of using melamine as a precursor to form carbon nitride through calcination and thermal polycondensation reaction. Calcination can be carried out in a muffle furnace. The calcination temperature is preferably 500-600°C, the time is preferably 3.3-4.5h, and the heating rate is preferably 1-10°C / min. Most preferably, the calcination temperature is 550°C, the time is 4h, and the heating rate is preferably 5°C / min.
[0025] Flake carbon nitride gC can be obtained by calcination 3 N 4 . The flake gC 3 N 4 After grinding, gC 3 N 4 The powder is a crude product. Then gC 3 N 4 The powdered crude product is washed and centrifuged to remove residual impurities, then dried to remove excess water, and then ground again to obtain gC 3 N 4Powder. In this step, the cleaning may be: washing with water and ethanol alternately 2 to 3 times. Those skilled in the art will appreciate that centrifugation is required after each washing to remove the supernatant before the next washing. The drying temperature is preferably 60 to 80°C; more preferably, the drying temperature is 70°C. The drying time is preferably 9 to 13 hours, more preferably 10 hours.
[0026] Step b) is to prepare N-deficient gC 3 N 4 , that is, NV-gC 3 N 4 powder step. Defect engineering is a method to improve gC 3 N 4 The method for improving the photocatalytic activity of the photocatalyst can adjust the band gap of the photocatalyst and improve the migration efficiency of the photogenerated charges. 3 N 4 The powder was calcined in an argon and hydrogen atmosphere. Heating under argon protection can prevent gC 3 N 4 At high temperatures, hydrogen reacts with oxygen or other gases in the air. 3 N 4 The nitrogen atoms in gC react to form ammonia or other nitrogen-hydrogen compounds. 3 N 4 These defects can serve as active sites and increase the activity of the material for photocatalytic reactions.
[0027] In the above step b), the volume ratio of argon to hydrogen is preferably 10:1, the calcination temperature is preferably 500-600°C, the time is preferably 0.5-1.5h, and the heating rate is preferably 1-10°C / min. More preferably, the calcination temperature is 550°C, the time is 1h, and the heating rate is 5°C / min. Step b) can be carried out in a tubular furnace to obtain NV-gC after calcination. 3 N 4 powder.
[0028] Step c) is a step of preparing a hydrothermal reaction raw material. In this step, sodium sulfide and cadmium acetate are first mixed uniformly in pure water. In this step, sodium sulfide and cadmium acetate react to form cadmium sulfide. Preferably, sodium sulfide and cadmium acetate are mixed uniformly in pure water by ultrasonic method. Then NV-gC is added. 3 N 4 powder, to obtain NV-gC 3 N 4 and CdS solid-liquid mixture, i.e., the raw material for the subsequent hydrothermal reaction. 3 N 4The mass ratio of powder, cadmium acetate and sodium sulfide is preferably (95-105): (1.6-3.6): (2-4). Most preferably, gC 3 N 4 The mass ratio of powder, cadmium acetate and sodium sulfide is 100:3:2.6.
[0029] Step d) is a key step in forming a heterojunction by a hydrothermal method. A heterojunction refers to an interface structure composed of two different materials, which has unique electronic properties and optoelectronic properties. With the development of science and technology, heterojunctions are increasingly widely used in optoelectronic devices, solar cells, sensors and other fields. This structure can optimize carrier separation and transmission by rationally designing the band structure and interface characteristics of the material, thereby improving the efficiency of the device. In photoelectric conversion, the heterojunction can effectively suppress the recombination of carriers and improve the utilization rate of photogenerated electrons. In this step, carbon nitride and cadmium sulfide are dissolved and recrystallized in the reaction, and the two are tightly bonded together to form a heterojunction. The hydrothermal method refers to a method for preparing a material in a sealed pressure vessel, using water as a solvent, and the powder is dissolved and recrystallized. Compared with other powder preparation methods, the powder obtained by the hydrothermal method has the advantages of complete grain development, small particle size, uniform distribution, and light particle agglomeration. In this step, the temperature of the hydrothermal reaction is preferably 155~165℃, and the time is preferably 11~13h. More preferably, the temperature of the hydrothermal reaction is 160° C. and the time is 12 h.
[0030] After the hydrothermal reaction, a mixture containing the target product was obtained, and then the surface impurities were removed by centrifugation and washing, and then the excess water was removed by drying, and finally CdS / NV-gC was obtained by grinding. 3 N 4 Heterojunction photocatalytic material. In this step, the cleaning may be: washing with water and ethanol alternately for 2 to 3 times. Those skilled in the art will appreciate that centrifugation is required after each washing to remove the supernatant before the next washing. The drying temperature is preferably 60 to 80°C; more preferably, the drying temperature is 70°C. The drying time is preferably 9 to 13 hours, more preferably 10 hours.
[0031] The CdS / NV-gC obtained in this step 3 N 4 In the heterojunction structure, gC 3 N 4 It has good light absorption and photogenerated charge separation capabilities, while CdS has high conductivity and tunable surface properties. The final CdS / NV-gC 3 N 4 Heterojunction photocatalytic materials can promote light absorption and current output, greatly improving the energy conversion efficiency and greatly extending the carrier lifetime compared to original carbon nitride.
[0032] Another embodiment of the present invention further provides a CdS / NV-gC 3 N 4 Heterojunction photocatalytic material, which is composed of NV-gC 3 N 4 Heterojunction composite material formed by CdS.
[0033] From the above content, it can be seen that the CdS / NV-gC provided by the embodiment of the present invention 3 N 4 Heterojunction photocatalytic materials and preparation methods thereof have the following advantages: 1. The preparation method uses melamine as a precursor to prepare NV-gC 3 N 4 , and then bonded tightly with cadmium sulfide through hydrothermal method to form a heterojunction. 3 N 4 It has good light absorption and photogenerated charge separation capabilities, while Cds has high conductivity and tunable surface properties. The heterojunction photocatalytic material formed by the two can promote light absorption and current output, greatly improving the energy conversion efficiency and greatly extending the carrier life compared to the original carbon nitride.
[0034] 2. The preparation method has the advantages of simple operation, mild reaction conditions, no pollution to the environment, and high catalytic activity of the product, so it can be widely used.
[0035] The inventors of this application found that the obtained CdS / NV-gC 3 N 4 The heterojunction photocatalytic material has an excellent degradation effect on the new pollutant-sulfonamide pollutants. Therefore, another embodiment of the present invention also provides the above CdS / NV-gC 3 N 4 The application of heterojunction photocatalytic materials in the degradation of sulfonamide pollutants. Specific applications include: The above CdS / NV-gC 3 N 4 The heterojunction photocatalytic material and the persulfate are mixed and uniformly dispersed in the sewage containing sulfonamide pollutants to obtain a water body to be treated; A xenon lamp equipped with a 400 nm filter is used as a light source to perform light treatment on the water body to be treated.
[0036] Persulfate activation uses the energy of visible light absorbed by photocatalytic materials. By absorbing the energy of visible light, photocatalytic materials can stimulate the generation of photogenerated charge pairs (i.e., electrons and holes). These photogenerated charge pairs further react with persulfate to produce highly oxidizing sulfate radicals; sulfate radicals have extremely high oxidizing ability and can effectively decompose organic pollutants and other target substances. Persulfate activation is usually carried out under relatively mild conditions without the need for high temperature or high pressure, which makes the reaction process more convenient and suitable for applications such as organic wastewater treatment and environmental remediation. Persulfate is preferably potassium sulfate powder. CdS / NV-gC 3 N 4 The mixing ratio of the heterojunction photocatalytic material and the potassium sulfate powder is preferably 1:1.
[0037] A xenon lamp with a 400nm filter provides the light source to excite the photocatalyst CdS / NV-gC 3 N 4 Produce photocatalytic activity. Ultraviolet light or visible light is used as the light source for photocatalytic reaction to stimulate gC 3 N 4 Electron-hole pairs are generated, which participate in redox reactions and degrade organic pollutants in the water. A 300W xenon lamp can be used in this step. After light treatment, separation and recovery can also be performed: the photocatalyst can be separated from the water sample by filtration, sedimentation or centrifugation for recycling and reuse.
[0038] The technical solution of the present invention is further described below in conjunction with specific embodiments: Example 1 (1) Take 15g of melamine in a 50ml crucible, cover it and place it in a muffle furnace for calcination. Set the heating rate to 5℃ / min, heat it to 550℃ and calcine it for 5h to obtain flake carbon nitride gC 3 N 4 The powder was then ground to obtain a powder, which was washed twice with water and ethanol alternately, centrifuged after each washing, and the supernatant was removed before the next washing; after the last washing, the powder was centrifuged and placed in a blast drying oven for drying (temperature 70°C, time 10h), and then ground again to obtain gC 3 N 4 The powder, the scanning electron microscope image is as follows Figure 1 shown.
[0039] (2) gC 3 N 4 The powder was placed in a quartz boat and passed through a tube furnace with high-purity argon and hydrogen (volume ratio 10:1). The heating rate was set to 5°C / min, and the temperature was raised to 550°C for calcination for 1 hour. After the tube furnace was cooled to room temperature, the solid was ground to obtain carbon nitride NV-gC with nitrogen defects. 3N 4 , the scanning electron microscope image is as follows Figure 2 shown.
[0040] (3) Weigh 3 mg of cadmium acetate and 2.6 mg of sodium sulfide, dissolve the two chemicals in 20 ml of ultrapure water, and mix them evenly by ultrasonication.
[0041] (4) 100 mg of nitrogen-deficient carbon nitride NV-gC 3 N 4 Mix with cadmium acetate and sodium sulfide solution, put into 50ml polytetrafluoroethylene lining, and then transfer to hydrothermal reactor, heat for 12h at 160℃. Centrifuge after reaction, remove supernatant and wash with water and ethanol alternately for 3 times, centrifuge after each washing, remove supernatant and then wash again; centrifuge after the last washing, put into air drying oven for drying (temperature 70℃, time 10h), and then grind to obtain CdS / NV-gC 3 N 4 Heterojunction photocatalytic material, the scanning electron microscope image is as follows Figure 3 As shown. Figure 3 It can be seen that CdS particles are evenly distributed in the stacked NV-gC 3 N 4 On the surface, it comes into close contact with carbon nitride to form agglomerates.
[0042] Sulfonamide Pollutant Degradation Test 1. Degradation performance of sulfadiazine and sulfamethoxazole 1. Take 20 mg of the photocatalytic material prepared in Example 1 and 20 mg of potassium persulfate powder, add them to 50 ml of 10 mg / L sulfamethoxazole solution, mix them evenly under ultrasonic, and place them under a 300 W xenon lamp (400 nm filter) for photocatalytic reaction. Sampling is performed every 15 minutes. After sampling, the samples are filtered through a 0.22 μm water filter membrane, and the filtered samples are analyzed by liquid chromatography.
[0043] 2. Same as step 1, except that the sulfonamide contaminant is replaced by sulfadiazine.
[0044] The degradation effect of two sulfonamide pollutants is shown in the figure Figure 4 As shown. Figure 4 It can be seen that after about 45 minutes of illumination, 10 mg / L of pollutants can be completely degraded.
[0045] 2. Comparison of the degradation performance of different photocatalysts on sulfamethoxazole Carbon nitride was prepared according to the method of step (1) in Example 1 as a control group; Defective carbon nitride was prepared according to the method of steps (1) to (2) in Example 1 as a control group; The degradation test was carried out using the method in step 1 of (I) above. The degradation effect diagram is shown in the figure below. Figure 5 As shown. Figure 5 It can be seen that: within one hour, the degradation of sulfamethoxazole by the original carbon nitride was only 25%, while the degradation of sulfamethoxazole by the defective carbon nitride after defect engineering was further improved to about 40%. Obviously, after the defective carbon nitride was loaded with CdS to form a heterojunction, the degradation efficiency was greatly enhanced, and the pollutant was completely degraded in only about 45 minutes.
[0046] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A method for preparing a CdS / NV-g-C3N4 heterojunction photocatalytic material, characterized in that: include: Step a), calcining melamine to obtain flaky g-C3N4, grinding the flaky g-C3N4 once, washing, centrifuging, drying and grinding again to obtain g-C3N4 powder; Step b), calcining the g-C3N4 powder under an argon and hydrogen atmosphere to obtain NV-g-C3N4 powder; Step c), mixing sodium sulfide and cadmium acetate in pure water, and then adding the NV-g-C3N4 powder to obtain a solid-liquid mixture containing NV-g-C3N4 and CdS; Step d), placing the solid-liquid mixture in a reactor for hydrothermal reaction, centrifuging the reaction mixture, washing, drying and grinding to obtain a CdS / NV-g-C3N4 heterojunction photocatalytic material.
2. The preparation method according to claim 1, characterized in that In the step a), the calcination temperature is 500-600° C., the time is 3.3-4.5 hours, and the heating rate is 1-10° C. / min.
3. The preparation method according to claim 1, characterized in that: In the step b), the volume ratio of argon to hydrogen is 10:1, the calcination temperature is 500-600° C., the calcination time is 0.5-1.5 h, and the heating rate is 1-10° C. / min.
4. The preparation method according to claim 1, characterized in that: In the step c), the mass ratio of g-C3N4 powder, cadmium acetate and sodium sulfide is (95-105): (1.6-3.6): (2-4).
5. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step d) is 155-165° C. and the time is 11-13 hours.
6. The preparation method according to claim 1, characterized in that: In the steps a) and d), the drying temperature is 60-80°C.
7. The preparation method according to claim 1, characterized in that: In the steps a) and d), the cleaning is specifically: washing with water and ethanol alternately 2 to 3 times.
8. A CdS / NV-g-C3N4 heterojunction photocatalytic material, characterized in that: It is prepared according to the method according to any one of claims 1 to 7.
9. Use of the CdS / NV-g-C3N4 heterojunction photocatalytic material according to claim 8 in the degradation of sulfonamide pollutants.
10. The use according to claim 9, characterized in that: include: The CdS / NV-g-C3N4 heterojunction photocatalytic material and persulfate described in claim 8 are mixed and uniformly dispersed in sewage containing sulfonamide pollutants to obtain a water body to be treated; A xenon lamp equipped with a 400 nm filter is used as a light source to perform light treatment on the water body to be treated.
Citation Information
Patent Citations
Preparation method of CdS / g-C3N4 composite photocatalyst material with Z-shaped heterojunction synthesized by hydrothermal method
CN112427045A
Cadmium sulfide and graphite phase carbon nitride composite photocatalyst as well as preparation method and application thereof
CN114602507A